MEMS-Reconfigurable Metamaterials and Antenna Applications - Tomislav Debogovic; Julien Perruisseau-Carrier (International Journal of Antennas and Propagation)
This paper reviews some of our contributions to reconfigurable metamaterials, where dynamic control is enabled by microelectromechanical systems (MEMS) technology. First, we show reconfigurable composite right-/left-handed transmission lines (CRLH-TLs) having state of the art phase velocity variation and loss, thereby enabling efficient reconfigurable phase shifters and leaky-wave antennas (LWA). Second, we present very low loss metasurface designs with reconfigurable reflection properties, applicable in reflectarrays and partially reflective surface (PRS) antennas. All the presented devices have been fabricated and experimentally validated. They operate in X- and Ku-bands.